Clinical Phenotype and Disease Course of Inflammatory Bowel Disease: A Comparison Between Sporadic and Familial Cases. Issue 7 (21st August 2021) - Saberzadeh-Ardestani, Bahar; Anushiravani, Amir; Mansour-Ghanaei, Fariborz; Fakheri, Hafez; Vahedi, Homayoon; Sheikhesmaeili, Farshad; Yazdanbod, Abbas; Moosavy, Seyed Hamid; Vosoghinia, Hasan; Maleki, Iradj; Nasseri-Moghaddam, Siavosh; Khosravi, Bardia; et al.
Abstract: Background: The role of genetic and environmental factors in inflammatory bowel disease's (IBD) clinical course is not fully clear. We aimed to assess the clinical phenotype, disease course, and prognosis of familial IBD in comparison with sporadic cases. Methods: We conducted a prospective national matched case-control study of registered IBD patients in the Iranian Registry of Crohn's and Colitis (IRCC) recruited from 2017 until 2020. Sporadic and familial IBD patients were matched based on age, sex, and disease duration. Data on demographics, past medical disease, family history of IBD, disease type, clinical phenotype, extraintestinal manifestations, IBD medications, IBD activity using the IBD-control-8 questionnaire and the Manitoba IBD index, emergency visits in the past 12 months, admissions in the past 3 months, history of colon cancer, IBD-related surgeries, and aggressive phenotype were gathered. Variable distributions were compared between sporadic and familial cases. Results: Overall, 5231 patients with ulcerative colitis (UC, 18.3% familial) and 1438 patients with Crohn's disease (CD, 16.7% familial) were registered in the IRCC. Age at diagnosis was similar between familial and sporadic cases. After matching, 3523 UC patients and 908 CD patients were enrolled in the study. Extraintestinal manifestations, UC extent, CD location and behavior, anti-TNF use, disease activity, colon cancer, IBD-related surgeries and the aggressive phenotype were similar between these sporadic and familial cases. Conclusions: The prevalence of familial UC and CD cases in Iran was more similar to western countries, and family history did not show a predictive value for disease phenotype, course, and outcomes in our study.